Multimedia demystified - Dowling, Jennifer Coleman. 4 0 16; 5 (New York : McGraw-Hill, 2012)
This practical guide provides a background on multimedia, and then delves into the elements that make up a successful multimedia project. You'll learn about software and hardware tools, digital photography, sound editing, web authoring with HTML, vector graphics, file formats, computer animation, and much more. Detailed examples and concise explanations make it easy to understand the material, and end-of-chapter quizzes and a final exam help reinforce key concepts-- Provided by publisher.
Includes index.
Keywords: 2 -- 0; 6; Multimedia systems; 20; 2